Relasi Bimbingan Yang Ditampilkan Dosen Terhadap Kreativitas Belajar Mahasiswa Prodi Pai Fakultas Tarbiyah Dan Ilmu Keguruan Iain Manado - Abd. Latif Samal; Nurhayati; Nasrudin Yusuf (Proceedings of Annual Conference on Islamic Educational Management, 2021)
The formulation of the problem in this study is to determine the extent of the functional relationship between the guidance relations displayed by the lecturer and the creativity of student learning. The method used in this study is the correlational method, which is to see the relationship between the two variables. The technique used is to distribute questionnaires to 96 student respondents of the Faculty of Tarbiyah and Teacher Training from semester 2 to semester 8. It is expected to represent all students in the Faculty of Tarbiyah and Teacher Training as many as 462 people. Academic Year 2018/2019 The analysis used is instrument reliability testing with alpha coefficient analysis where the results obtained variable X is r count = 0.9551 and r list = 0.05 dk 20 is = 0.377. While the variable Y obtained r arithmetic = 0.93 r list = 0.05 dk 20 is r = 0.377, it turns out that r count is greater than r list or 0.93 > 0.377. From the results of testing the first hypothesis and the second hypothesis in the calculation above, it can be concluded that the weight of the relationship between the guidance relationship displayed by the lecturer and the student's creativity of 62% is quite significant and the remaining 38% is influenced by other factors. The results of this study provide information to lecturers in order to create family relationships with students so that students are more active in learning.